THE COLONIZING OF EXISTENTIAL SPACE - Botha, Ryan (PINS-Psychology in Society, 2025)
Greenberg, Gary (2010) Manufacturing depression: The secret history of a modern disease. London: Bloomsbury Publications. ISBN 978-1-4088-0190-1pbk. Pages 432. “Depression” is a ubiquitous term within professional and lay discourses on mental health. As a psychiatric meta-signifier, the term encompasses the vast expanses of existential malaise that characterize the human condition. But what exactly is depression and to what extent does its ontological integrity stand up to critical interrogation? Manufacturing depression represents a deeply insightful engagement with this very issue. Part memoir, part history, part axe to grind, the book critically examines the rapid expansion of the depression industry with a view to its implications for how modern society has come to understand its existential anguish. Its author, Gary Greenberg, as both a psychotherapist and individual sufferer of depression proves a dependable guide through this deeply personal and political terrain.